2015
DOI: 10.1007/s40520-015-0423-3
|View full text |Cite
|
Sign up to set email alerts
|

Femoral cortical index: an indicator of poor bone quality in patient with hip fracture

Abstract: A significant correlation among low values of FCI, comorbidities, severe hypovitaminosis D. and BMD in patients with hip fractures has been found. FCI could be a useful tool to evaluate bone fragility and to predict fracture risk even in the normal and osteopenic BMD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In fact, fragility fracture risk depends not only on loss of BMD but also on alterations of bone quality [27][28][29] and calcium, 99% of which is included in the skeleton, predominantly affects bone mineralization [2]. A very low daily dietary calcium intake (<400 mg/day) probably leads to a depletion in body calcium content which could compromise good bone mineralization, thus increasing fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, fragility fracture risk depends not only on loss of BMD but also on alterations of bone quality [27][28][29] and calcium, 99% of which is included in the skeleton, predominantly affects bone mineralization [2]. A very low daily dietary calcium intake (<400 mg/day) probably leads to a depletion in body calcium content which could compromise good bone mineralization, thus increasing fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are studies stating that the chosen anesthetic method had no effect on the mortality or outcome [7]. Bone tissue quality disorders linked to osteoporosis, vitamin D deficiency, and other comorbidities increase the risk of hip fracture in elderly patients [8]. In our study, the mean age of patients given THP treatment was found to be lower than patients undergoing PHP or PFN treatments.…”
Section: Discussionmentioning
confidence: 50%
“…The proximal femoral bone quality, which is considered 1 of the morphological features, related to proximal femoral fracture, was previously assessed by plain radiography and pelvic CT. The relation to hip fracture was evaluated (2, 23, 24). Feola et al (24) found that the risk of hip fracture was increased in patients with low CI (24).…”
Section: Discussionmentioning
confidence: 99%